The evaluation of temperament and quality of life in patients with polycystic ovary syndrome. (4th March 2017) - Ozcan Dag, Zeynep; Alpua, Murat; Isik, Yuksel; Buturak, S. Visal; Tulmac, Ozlem B.; Turkel, Yakup
Abstract: Aims : To evaluate the temperament and quality of life (QoL) of patients with PCOS. Materials and methods : Fifty-three adult patients with PCOS and 38 healthy controls were enrolled in the study. Demographic characteristics including age, education and body mass index (BMI) were recorded. Affective temperaments were assessed by the temperament evaluation of Memphis, Pisa, Paris and San Diego-autoquestionnaire version (TEMPS-A) scale. The general health-related quality of life (HRQoL) instrument used in this study was short Form 36. Hospital anxiety and depression scale (HADS) were also performed. Results : The patients with PCOS had significantly higher rates of depressive, anxious and hyperthymic scores compared to controls. The PCOS patients had significantly lower mean SF-36 health summary scores. Conclusions : TEMPS-A seems to be an easy and reliable test to evaluate temperament in PCOS patients.